Analisis Komponen Laba Rugi pada Perusahaan LQ45 Periode 2014-2019 - Aulia Shandy Pramesta Cahyani; Nanu Hasanuh (Sosio e-Kons, 2022)
The COVID-19 pandemic has greatly impacted many corporate sectors, including LQ45 companies, which are also feeling the consequences. Many companies have suffered losses and even bankruptcies due to COVID 19 since March 2020. One of the things that really have an impact is the sales department which later affects net profit. Given that the pandemic is still not over, many companies are trying to adjust so that sales can continue to generate maximum numbers by preparing many plans. Therefore, the author is interested in conducting an analysis related to the profit and loss component of the LQ45 company because the company always creates considerable sales. The proxies of the profit and loss component use Net Profit and its analysis tools in view of Net Sales and Income Tax Expense. This study aims to determine whether there is an influence between Net Sales and Income Tax expenses on Net Profit partially or simultaneously. The sample collection system chosen was purposive sampling and there were 6 companies out of 45 companies listed on the Indonesia Stock Exchange (IDX). Furthermore, the data analysis chosen is descriptive and verifiable data analysis using the SPSS 26 application. The results showed that there was no influence between Net Sales and Net Profit partially, but there was an influence between Income Tax Expense on Net Profit in general. Furthermore, there is an influence between Net Sales and Income Tax Expense on Net Profit simultaneously.